2015
DOI: 10.15270/51-2-413
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Adolescents’ Participation in Decision Making in Related Foster Care Placements in South Africa

Abstract: Since the United Nations Convention on the Rights of the Child was adopted in 1989, children have a right to express their views and participate in matters concerning them. This aspect of participation is also encompassed in legislation in South Africa. This paper explores the participatory decision-making experiences that adolescents have relating to their foster care placements by conducting a qualitative research study. Findings indicate that a minority of adolescents were included in the decision-making pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…There were 30 publications that were analysed from the EbscoHost databases Agere, Tanga, & Kang'ethe, 2017;Ali, 2017;Couzens, 2011;Hope, & Van Wyk, 2018;Kaonga, Batavia, Philbrick, & Mechael, 2016;Malherbe, & Häefele, 2017;Mathews, 2013;Mathews, & Martin, 2016;Matthias, 2015;Nhedzi & Makofane, 2015;Okem, 2017;Patel & Hochfeld, 2011;Rosenberg, Pettifor, Myers, Phanga, Marcus, Bhushan & Mtwisha, 2017;Schiller, 2017;Schmid, 2014;Siljeur, 2016 Strydom, 2010;Schiller, 2015;Sibanda & Lombard, 2015;Singh & Singh, 2014;Steyn, Van Wyk & Kitching, 2017;Strydom, 2010;Strydom, et al 2017;Van Niekerk & Matthias, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 30 publications that were analysed from the EbscoHost databases Agere, Tanga, & Kang'ethe, 2017;Ali, 2017;Couzens, 2011;Hope, & Van Wyk, 2018;Kaonga, Batavia, Philbrick, & Mechael, 2016;Malherbe, & Häefele, 2017;Mathews, 2013;Mathews, & Martin, 2016;Matthias, 2015;Nhedzi & Makofane, 2015;Okem, 2017;Patel & Hochfeld, 2011;Rosenberg, Pettifor, Myers, Phanga, Marcus, Bhushan & Mtwisha, 2017;Schiller, 2017;Schmid, 2014;Siljeur, 2016 Strydom, 2010;Schiller, 2015;Sibanda & Lombard, 2015;Singh & Singh, 2014;Steyn, Van Wyk & Kitching, 2017;Strydom, 2010;Strydom, et al 2017;Van Niekerk & Matthias, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Prompted by the UN Convention on the Rights of the Child, several scholars have expounded on the need for greater participation of children as they make critical decisions about their lives when involved in the child welfare system (Cook, Blanchet-Cohen & Hart, 2004;Moyo, 2015;O'Kane, 2013;Viviers & Lombard, 2013). Schiller (2015) demonstrated in a qualitative research study the need for greater participation of adolescents in foster care during decision-making processes. In a similar vein, Strode (2015) proposes that South African legislation has become so restrictive that children's participation in research is severely limited.…”
Section: Figure 4 Adjusted Type and Number Of Participantsmentioning
confidence: 99%
“…Social workers in NGOs are often expected to perform statutory social work and implement prevention, and intervention programmes. Many other authors have also found that inadequate funding leads to an inability to address the structural constraints such as lack of human capital and resources, lack of basic organisational resources such as vehicles or fuel to conduct home visits, and a burdensome caseload (Schiller, 2015Strydom, 2010Strydom, Spolander, Engelbrecht & Martin, 2017). Because of these limitations, there is a major emphasis on statutory services and crisis management (Strydom, Schiller & Orme, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Through these laws and programmes, the South African state has encouraged respect for the views of the child in schools, families and the care and judicial systems, as well as promoted public awareness of children’s participatory rights (Department of Women, Children and People with Disabilities, 2013: 18). Practice realities in the field of foster care, however, indicate that children and adolescents specifically are not always included in decisions and matters affecting them (Schiller, 2015: 8).…”
Section: Introductionmentioning
confidence: 99%